The analysis of cell damage of liver and kidney among alcoholics in Yogyakarta, Indonesia - S Suhartini; Hendro Widagdo; Yudha Nurhantari; Idha Arfianti Wiraagni (Journal of the Medical Sciences (Berkala Ilmu Kedokteran), 2019)
Alcohol tends to disrupt the organs function of human body, even can cause serious and chronic damage. In Indonesia, the data on cell damage taken from organs including the livers and kidneys among alcoholics are still practically unknown. The aim of this study was to compare the differences of organs’ cell disturbance between alcoholics and non-alcoholics in Yogyakarta, Indonesia. A crosssectional study was conducted among 197 people in Yogyakarta, including 96 alcoholics and 101 non-alcoholics. The material of the study was taken from venous blood samples. A kinetic photometric test was conducted to obtain data on blood-chemical markers’ value of livers (SGOT, SGPT, and GGT), and kidneys (BUN and serum creatinine). The data werethen analyzed by Chi square test.From a total of 96 alcoholics, 83.6% are males and 16.4% are females who consumed alcohol for an average of 16 years, with 51.6% routinely consuming it daily. The kind of alcohol they consumed was single-brand (59.8%). Based on 25th percentile (GGT), on 50th percentile (SGOT, GGT), and on 75th percentile (SGPT, GGT), the alcoholics had higher proportion value of liver marker disturbance than non-alcoholics which was statistically significant (p<0.05). Based on the 50th and 75th percentiles, the alcoholics also had higher proportion value on kidney marker (BUN) damage than non-alcoholics which was statistically significant (p<0.05). There were significant differences in GFR values between males and females (p<0.05), males had kidney cell damage 7.9 times more than females. There was no significant difference in the value of GFR between alcoholics and non-alcoholics. In conclusion, the alcoholics hassignificantly higher proportion value of blood-chemical markers than that non-alcoholics. The GFR values between males and females are also significantly different, and males had kidney cell damage 7.9 times more than that of females.